THE FRAMING OF WOMEN’S IDEAL BODY IN AMERICAN SOCIETY IN INSTAGRAM ILLUSTRATIONS BY JULIE HOUTS (@JOOLEELOREN) - Ni Wayan Eka Jayanti; Ida Rochani Adi (Rubikon : Journal of Transnational American Studies, 2020)
This study aims to learn about the framing of women’s ideal body in Julie Houts’ illustrations and the factors that shape the frames. Conducted within American Studies, this study borrows Entman’s framing theory. This study applies qualitative and inductive methods to interpret the data. This study found that the framing highlights how women’s ideal body is limited to one body type. A thin, youthful appearance is often considered the ideal appearance for women. Tan skin is another aspect regarded as the ideal appearance for women. Thinness, youthful appearance, and tan skin are desired because they signify health, reflecting society’s obsession with health. The obsession with health often renders health a matter of appearance and gives power to those who look “healthy.” The benefits of having the ideal body often outweigh the risks women may bear from pursuing the ideal body. As women’s ideal body is limited to a thin, youthful appearance with tan skin, discrimination often occurs against women who do not match the ideal. Circumstances in society and the perception of women’s bodies become the factors that shape what is considered the ideal body.